Life beyond growth? Rural depopulation becoming the attraction in Nagoro, Japan's scarecrow village. Issue 5 (3rd September 2021) - Hashimoto, Atsuko; Telfer, David J.; Telfer, Sakura
ABSTRACT : Rural villages in Japan are rapidly ageing and depopulating. On Shikoku Island, in the remote mountainous Iya Valley, is the village of Nagoro. Residents who have left or passed away have been replaced with ' kakashi ' or scarecrows in the form of life-like dolls. Currently, scarecrows outnumber the village residents and appear throughout the community—waiting at bus stops, working the fields, and studying at the closed school. The attempt to preserve village life and identity through the scarecrow displays has begun to attract the attention of media and tourists. This paper examines this emerging rural tourism attraction in the context of Japanese rural depopulation and peripheralisation. Nagoro is representative of many Japanese villages where the rural lifestyle is disappearing. It has adopted a unique form of quiet resistance to the ending of an era viewed in the context of museumisation and abandoned landscapes. Rural communities are transitioning finding themselves between government rejuvenation policies and learning to live beyond growth.